1994
DOI: 10.1180/minmag.1994.058.393.16
|View full text |Cite
|
Sign up to set email alerts
|

The roedderite-chayesite series from Spanish lamproites: crystal-chemical characterization

Abstract: Members of the roedderite-chayesite series in lamproites from Cancarix (SE Spain), crystallized from late magmatic residua under low PH20, high temperature (~ l l00~ oxidizing conditions. They exhibit the following main chemical variations: 0.14 ~< Na ~< 0.62 atoms per formula unit ( The 12-coordinated C site, located between two double rings of T1 tetrahedra, is occupied mainly by K and subordinately by Na. Furthermore, Na occupies the partially empty nine-fold coordinated B site which occurs both in the idea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 11 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…6). Chemical data make it possible to assume that the mineral is a Zn-and Cu-rich variety of roedderite, ideally KNaMg 5 [Si 12 O 30 ] (Alietti et al, 1994), or its hypothetic Mg−(Cu/Zn)-ordered analogue. Table 3.…”
Section: Cyclosilicate the Cuzn-rich Analogue Of Roedderitementioning
confidence: 99%
“…6). Chemical data make it possible to assume that the mineral is a Zn-and Cu-rich variety of roedderite, ideally KNaMg 5 [Si 12 O 30 ] (Alietti et al, 1994), or its hypothetic Mg−(Cu/Zn)-ordered analogue. Table 3.…”
Section: Cyclosilicate the Cuzn-rich Analogue Of Roedderitementioning
confidence: 99%
“…Enstatite in association with richterite, richterite fragment with Na‐Al augite inclusion, and the coexistence of richterite and roedderite in the melt matrix breccia SP7#2012‐3 indicate co‐ or sequential crystallization of these phases from the common melt, probably on the late stage of its evolution. In terrestrial rocks, richterite was observed in an aggregate with roedderite and crystallized at temperature ~1000 °C in lamproites (Alietti et al 1994). It is notable that synthetic fluororichterite glass ceramic crystallizes fluororichterite and roedderite at temperatures 900 and 960 °C (Denry and Holloway 2006).…”
Section: Discussionmentioning
confidence: 99%